Correlation of pharmacokinetic dispositionof methotrexate and serum cytokine levels in rheumatoid arthritis patients (Bangladesh Journal of Medical Science, 2022)
Objective: Methotrexate is the principal basic anti-inflammatory medication used in the rheumatoid arthritis treatment.Therefore, research into its effect on cytokine concentrations may help improve the effectiveness of disease treatment.Study aim: was to investigate the neffect of methotrexate therapy on the blood content of proinflammatory cytokines in RA patients, as well as define the relation of proinflammatory cytokine blood concentration to clinical and laboratory disease features and methotrexate pharmacokinetics.Material and methods: Sixty-five patients with rheumatoid arthritis (46 women and 19 men; average age 50.83± 8.91 years) underwent an examination.Thirty-two patients (26 women and 6 men) participated in studyingmethotrexate pharmacokinetics.Results and Discussion: The course of rheumatoid arthritis is accompanied by a significant increase of TNF-α (40.36±4.01 pg/ml), IL-1β (17.68±1.74 pg/ml), andIL- 6(8.39±0.46pg/ml) in the blood.Oral administration of methotrexate (MT) for patients with rheumatoid arthritis promotes persistent elimination of clinical disease symptoms and reduced production of proinflammatory cytokines:TNF-α drops by 2.08 times (p